Using a systems approach to evaluate a circulating nurse's work patterns and workflow disruptions. (July 2019) - Neyens, David M.; Bayramzadeh, Sara; Catchpole, Kenneth; Joseph, Anjali; Taaffe, Kevin; Jurewicz, Katherina; Khoshkenar, Amin; San, Dee; ,
Abstract: The physical environment affects how work is done in operating rooms (OR). The circulating nurse (CN), in particular, requires access to and interacts with materials, equipment, and technology more than other OR team members. Naturalistic study of CN behavior is therefore valuable in assessing how OR space and physical configuration influences work patterns and disruptions. This study evaluated the CNs' work patterns and flow disruptions (FD) by analyzing 25 surgeries across three different ORs. The OR layouts were divided into transitional and functional zones, and the work of CNs was categorized into patient, equipment, material, and information tasks. The results reveal that information tasks involve less movement than other types of work, while across all ORs, CNs were more likely to be involved in layout and environmental hazard FDs when involved in patient, material, or equipment-related tasks compared to information tasks. Different CN work patterns and flow disruptions between ORs suggest a link between OR layout and a CN's work. Future studies should examine how specific layout elements influence outcomes. Highlights: An operating room layout can influence work patterns of circulating nurses. Smaller zones may predispose circulating nurses to more flow disruptions. Layout can influence travel distance and number of zones travelled through. Physical environment is an influential element of the work system.